The Sociological Assessment of the Behavioral Abnormalities of Students (Case Study: Shiraz City) - mohammadtaghi iman; leyla bahmani; maryam sadat delavar (توسعه اجتماعی, 2016)
The assumption of the present paper is that loyalty to the religious beliefs, intimate relationships with family members and friendship groups can be influential on behavioral abnormalities among the teenagers. To study that assumption, the required data was gathered through the survey and using questionnaires and choosing a sample of 385 girls from among the high school students; the sampling method was the multistage random. The findings show that the increase of religious commitments and intimate relationships with family members would reduce the behavioral abnormalities of students; it also affirms the high rate of behavioral abnormalities in students who have more relationships with people who break the norms; the regression results suggest that the religious commitments and relationships with friendship groups would enter the equation in order of their importance in determining the dependent variable and they can describe about 49 percent of the variance of the dependent variable (R2 = 49%).